The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s12039-007-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium deoxycholate and sodium cholate on DPPC vesicles: A fluorescence anisotropy study with diphenylhexatriene

Abstract: Effects of two bile salts, namely sodium deoxycholate (NaDC) and sodium cholate (NaC), on DPPC small unilamellar vesicles have been investigated using the steady-state fluorescence anisotropy (r ss ) of diphenylhexatriene (DPH) as a tool. It was found that the variation of r ss is sensitive enough to monitor different stages of interaction of bile salts with DPPC vesicles. NaDC induced significant changes in the membrane well below its CMC (6 mM). Even at 4 mM, which is still lower than the CMC, the phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Based on the research published by Subuddhi & Mishra (2007), vesicles solubilization by bile salts occurs in three stages depending on bile salt concentrations. At low bile salts concentration, the surfactants partition into the lipid bilayer.…”
Section: Vesicles Destruction In Gitmentioning
confidence: 99%
“…Based on the research published by Subuddhi & Mishra (2007), vesicles solubilization by bile salts occurs in three stages depending on bile salt concentrations. At low bile salts concentration, the surfactants partition into the lipid bilayer.…”
Section: Vesicles Destruction In Gitmentioning
confidence: 99%
“…This is also supported by the slightly higher blue shift in the emission maximum and higher fluorescence anisotropy value of NB in NaDC than in NaC micelles. NaDC is known to form large and firm micelles that provide a relatively more hydrophobic microenvironment as compared to that of NaC to the solubilized molecules [26][27][28][29][30]32]. …”
Section: Fluorescence Quenching Studiesmentioning
confidence: 99%
“…They are referred to as biosurfactants taking into account their capacity to solubilize and emulsify cholesterol, bilirubin, lecithin, lipids and fat soluble vitamins in living organisms [26][27][28][29][30][31]. Apart from their biological importance, bile salts also have got much recognition as delivery systems for medicines, cosmetics and several other chemicals and are also used as membrane penetration enhancers in drug formulations [31].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the membranolytic resistance of membranes with unsaturated acyl chains [59], it is observed that phospholipids with saturated acyl chains [56,92] are more easily transformed into micelles. In other words, less detergent is required for the solubilisation of saturated bilayer membranes compared to unsaturated lipid analogues.…”
Section: Influence Of the Saturation Degree Of The Acyl Chains Of Thementioning
confidence: 99%